2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.26745
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Entrepreneurial Mindset in Engineers: An Application of the Three C's (Creativity, Curiosity, and Connections) in a Collaborative Summer Mega-Course

Abstract: Scott Kirkpatrick is an Assistant Professor of Physics and Optical Engineering at Rose-Hulman Institute of Technology. He teaches physics, semiconductor processes, and micro electrical and mechanical systems (MEMS). His research interests include heat engines, magnetron sputtering, and nanomaterial self-assembly. His masters thesis work at the University of Nebraska Lincoln focused on reactive sputtering process control. His doctoral dissertation at the University of Nebraska Lincoln investigated High Power Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 2 publications
1
11
0
Order By: Relevance
“…Within the domain experiences (curricular, co-curricular, and research), it was clear that students found curricular experiences to be the most prevalent in nurturing their EM, making up 39.34% of the total number of experiences. It has been shown throughout literature that curricular interventions are extremely beneficial in introducing creative and entrepreneurial thinking to students to better prepare them for their future careers (Bernal et al., 2017; Fraley et al., 2018; Ghazi Nezami et al., 2016; Huerta et al., 2017; Jensen & Schlegel, 2017; Kim et al., 2016; Kirkpatrick et al., 2016; Riofrío et al., 2015; Wang, 2017). Much of these studies are focused on analysis of EM growth immediately after an intervention takes place (Ali et al., 2012; Hsiao, 2013; Kim et al., 2016), but this study shows that after giving students time to reflect across multiple experiences, they still consider curricular interventions to be the most beneficial to their EM development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the domain experiences (curricular, co-curricular, and research), it was clear that students found curricular experiences to be the most prevalent in nurturing their EM, making up 39.34% of the total number of experiences. It has been shown throughout literature that curricular interventions are extremely beneficial in introducing creative and entrepreneurial thinking to students to better prepare them for their future careers (Bernal et al., 2017; Fraley et al., 2018; Ghazi Nezami et al., 2016; Huerta et al., 2017; Jensen & Schlegel, 2017; Kim et al., 2016; Kirkpatrick et al., 2016; Riofrío et al., 2015; Wang, 2017). Much of these studies are focused on analysis of EM growth immediately after an intervention takes place (Ali et al., 2012; Hsiao, 2013; Kim et al., 2016), but this study shows that after giving students time to reflect across multiple experiences, they still consider curricular interventions to be the most beneficial to their EM development.…”
Section: Discussionmentioning
confidence: 99%
“…Though EE and the assimilation of EM are necessary for all students, EM in engineering has been an area of particular focus over the last several years (Huang-Saad et al., 2018). EM integration through curricular activities has been shown to have a positive impact on undergraduate engineering students' EM development (Bernal et al., 2017; Fraley et al., 2018; Ghazi Nezami et al., 2016; Huerta et al., 2017; Jensen & Schlegel, 2017; Kim et al., 2016; Kirkpatrick et al., 2016; Riofrío et al., 2015; Wang, 2017). Interventions in first year engineering are widely studied, often within general engineering courses that utilize design and problem solving (Huerta et al., 2017; Jensen & Schlegel, 2017; Riofrío et al., 2015; Wang, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The PBL approach allows this way of acquiring entrepreneurship skills. Furthermore, the potential outcomes of PBL are aligned with the three C's of the entrepreneurial mindset (Creativity, Curiosity, and Connections) [5] and there are several reported uses of PBL for Entrepreneurship teaching [2], [6], [7], [8], [9].…”
Section: Pbl As An Enabler For An Entrepreneurship Mindsetmentioning
confidence: 96%
“…Share previous work of group members, to establish an idea of each other's knowledge level and way of working.4 Adding cultural activities early on in the project and also at the start of the return visit, makes for a better team spirit 5. The timespan for the most recent project was about 8 weeks, with 6 weeks of virtual collaboration.…”
mentioning
confidence: 99%